Book Review: Lobbying the European Union: Institutions, Actors and Issues, David Coen and Jeremy Richardson (eds.) - Alexandra Pop (Romanian Journal of European Affairs, 2013)
The volume “Lobbying the European Union: Institutions, Actors and Issues”, collects 16 articles on interest group politics at EU level, focusing on the main elements of European lobbying – the existing relations between the EU institutions and the special interests, the main differences between NGO and business lobbying, the specific lobbying strategies adopted in EU’s main policy sectors or lobbying regulations. The volume captures the main changes that took place on the European lobbying scene in the last two decades, period in which most EU institutions developed new points of access for lobbyists, while the interest groups became more specialized. The success of an EU lobbying campaign seems to be determined by a combination of various factors such as: a good knowledge of the EU environment, a wise usage of both financial resources and expertise, direct lobbying complemented by an efficient usage of domestic routes and the capability of creating smart alliances.